Between traditions and globalization: value orientations of Kazakhstani youth - Buribayev, Yermek; Khamzina, Zhanna; Buribayeva, Amina (Frontiers in Sociology, 2025)
IntroductionIn this manuscript, a study of the social values of Kazakhstani youth is presented in the context of the new social reality of independent Kazakhstan. The purpose of this work is to identify the similarities and differences in the value priorities of youth compared to national trends, as well as to determine the factors influencing the formation of values in modern Kazakhstani society.MethodsThe methodological basis of the study is a sociological survey conducted among Kazakhstani youth, whose results were compared with the 2018 World Values Survey (WVS) data. Such a comparative analysis enables a deeper understanding of the specific characteristics of the value orientations of the younger generation.ResultsThe value orientations of Kazakhstani youth were analyzed and compared with the results of the 2018 WVS conducted in Kazakhstan. The identified trends reflect the influence of globalization and socio-economic changes on the value priorities of youth.DiscussionThe findings have practical significance for the development of effective youth policies that take into account the specific value orientations and needs of the younger generation. This approach contributes to their social integration and supports the sustainable development of Kazakhstan.